Assessment of naloxone as a therapeutic for inhaled carfentanil in the ferret. (2020) - McCranor, Bryan J.; Jennings, Laura; Tressler, Justin; Tuet, Wing Y.; DeLey Cox, Vanessa E.; Racine, Michelle; Stone, Samuel; Pierce, Samuel; Pueblo, Erin; Dukes, Aliyah; Litvin, Samantha R.; Leyden, Melissa R.; et al.
Graphical abstract: Highlights: Carfentanil aerosol induced profound cardiorespiratory and physiological effects. Carfentanil was bioavailable approximately 3 times longer than naloxone. Naloxone was able to rapidly reverse the effects of a lethal exposure. Abstract: Carfentanil is a powerful synthetic opioid that is approximately 100 times more potent than fentanyl and 10, 000 times more potent than morphine. Carfentanil was originally intended to be used as a sedative for big game animals in a veterinary setting, but it is becoming increasingly recognized as a public health concern. We set out to investigate the effectiveness of naloxone against a potentially lethal dose of inhaled carfentanil in male ferrets. Ferrets were implanted with telemetry devices to study cardiac parameters and exposed to aerosolized carfentanil in a whole-body plethysmography chamber to record respiratory parameters. We observed profound respiratory depression in exposed animals, which led to apneic periods constituting 24–31 % of the exposure period. Concomitant with these apneic periods, we also observed cardiac abnormalities in the form of premature junctional contractions (PJCs). At our acute exposure dose, lethal in 3 % of our animals, naïve ferrets were unresponsive and incapacitated for a total of 126.1 ± 24.6 min. When administered intramuscularly at human equivalent doses (HEDs) of either 5 mg or 10 mg, naloxone significantly reduced the time that ferrets were incapacitated following exposure, although we observed no significant difference in the reduction of time that the animals were incapacitated between the treatment groups. Naloxone was able to quickly resolve the respiratory depression, significantly reducing the frequency of apneic periods in carfentanil-exposed ferrets. Our results suggest that naloxone, when administered via intramuscular injection following incapacitation, is a viable treatment against the effects of a potentially lethal dose of inhaled carfentanil.